2017
DOI: 10.1128/jvi.00763-17
|View full text |Cite
|
Sign up to set email alerts
|

A Map of the Arenavirus Nucleoprotein-Host Protein Interactome Reveals that Junín Virus Selectively Impairs the Antiviral Activity of Double-Stranded RNA-Activated Protein Kinase (PKR)

Abstract: Arenaviruses are enveloped negative-strand RNA viruses that cause significant human disease. These viruses encode only four proteins to accomplish the viral life cycle, so each arenavirus protein likely plays unappreciated accessory roles during infection. Here we used immunoprecipitation and mass spectrometry to identify human proteins that interact with the nucleoproteins (NPs) of the Old World arenavirus lymphocytic choriomeningitis virus (LCMV) and the New World arenavirus Junín virus (JUNV) strain Candid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 56 publications
8
75
1
3
Order By: Relevance
“…In conclusion, we have provided a detailed map of JUNV virus interactions with the human proteome and identified several host factors required for JUNV infection. This work, combined with our previous proteomics studies (74,96), represents a crucial step in understanding the protein networks hijacked by arenaviruses to drive the virus life cycle. This study highlights the important role that the ESCRT pathway plays in driving infectious JUNV particle release, while further demonstrating the diversity exhibited among arenaviruses in their use of ESCRT machinery for the production of different classes of virus particles.…”
Section: Discussionmentioning
confidence: 89%
“…In conclusion, we have provided a detailed map of JUNV virus interactions with the human proteome and identified several host factors required for JUNV infection. This work, combined with our previous proteomics studies (74,96), represents a crucial step in understanding the protein networks hijacked by arenaviruses to drive the virus life cycle. This study highlights the important role that the ESCRT pathway plays in driving infectious JUNV particle release, while further demonstrating the diversity exhibited among arenaviruses in their use of ESCRT machinery for the production of different classes of virus particles.…”
Section: Discussionmentioning
confidence: 89%
“…While our manuscript was in preparation, King et al reported that infection with the Candid#1 vaccine strain of JUNV activated the PKR response in infected cells and that small interfering RNA (siRNA)-mediated knockdown of PKR had no impact on viral propagation (50). Furthermore, JUNV NP is shown to interact with PKR in infected cells, suggesting that JUNV NP might locally inhibit PKR activity, thereby facilitating viral protein synthesis.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest a phenotypic difference in the impact of virus infection on protein synthesis between the vaccine and pathogenic strains of JUNV, which remains to be investigated in future studies. Another potential way to explain the observed differences is that we prepared and used recombinant virus stocks that are likely less heterogeneous than the vaccine Candid#1 strain used in the aforementioned study (50).…”
Section: Discussionmentioning
confidence: 99%
“…To date, lists of host-cell proteins associated with various arenavirus infections have been established, providing new bases to investigate the potential roles of such interactions during the course of infection. With the exception of one study, which focused on the proteins of cellular origin associated with the Z protein of JUNV, most reports have focused on the NP and L interactomes during JUNV and LCMV infection [44][45][46][47][48]. However, these reports were based on the expression of tagged viral proteins through transfection or infection with genetically modified viruses and the identification of associated host-cell partners after purification and mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%